Functional and Morphological State of Gastrointestinal Tract Cells in Patients with Rheumotoid Arthritis - Miralievna, Boltaeva Mayram (European Journal of Life Safety and Stability (2660-9630), 2022)
This review is devoted to characterizing the cause of the risk of damage to the gastrointestinal tract in patients with rheumatoid arthritis. One of the urgent problems of modern medicine is the gastrointestinal tract lesion in rheumatoid arthritis. The issues of prevalence and risk factors of chronic gastrointestinal disease are considered. The gastrointestinal tract is affected in rheumatoid arthritis more often than it is diagnosed. As a result, early diagnosis of gastrointestinal lesions in patients with rheumatoid arthritis has an important clinical and prognostic value. Possible morphological variants and mechanisms of damage to the gastrointestinal tract are also considered. In rheumatoid arthritis, the occurrence of chronic gastrointestinal disease depends primarily on the duration of the disease and the nature of the inflammatory process. These data are fully confirmed at the present time. The problem of gastrointestinal lesions in rheumatoid arthritis is poorly understood and requires further research.